Association between participation in the Northern Finland Birth Cohort 1966 study and use of psychiatric care services - Kerkelä Martta; Gissler Mika; Nordström Tanja; Veijola Juha (Public Library of Science, 2025)
Aims
In most population-based epidemiological follow-up studies the aim is not to intervene in the life of the participants. Although the idea is not to intervene, being a member of the longitudinal follow-up study and studies conducted during follow-up may affect the target population. A population-based study including mental health enquiries might reduce the unmet need for psychiatric treatment by motivating people to seek treatment for their psychiatric ill-health. We examined the use of psychiatric care services in the population born in the year 1966 in Northern Finland, of whom 96.3% are participants in the prospective Northern Finland Birth Cohort 1966 (NFBC1966).
Methods
As a study cohort we used people born in 1966 in Northern Finland (n = 11 447). The comparison cohort included all the people born in the years 1965 and 1967 in the same geographical area (n = 23 339). The follow-up period was from age 10 to 50 years. The outcome measure was the use of psychiatric care services, which was analysed using Cox Proportional Hazard regression and Zero-Truncated Negative Binomial Regression.
Results
People born in 1966 in Northern Finland did not differ from those born in 1965 and 1967 in terms of the outcome measure.
Conclusions
We found no association between participation in an epidemiological follow-up study and the use of psychiatric care services. The NFBC1966 may be regarded as a representative at the population level in terms of psychiatric outcomes despite the personal follow-up of the birth cohort. The associations of participation in epidemiological follow-up studies have previously been under-examined, and the results need to be replicated.